Investigating Self-Efficacy in Arabic Vocabulary Learning Through Needs Analysis: Evidence from the ATEM Framework - Widiya Yul; Riko Andrian (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2026)
Self-efficacy plays an important role in vocabulary learning; however, little is known about learners' self-efficacy conditions before instructional interventions in Arabic as a Foreign Language (AFL) contexts. This study aimed to identify students' self-efficacy needs in Arabic vocabulary learning as a basis for developing interventions through the Arabic Teaching Efficacy Model (ATEM). A sequential exploratory mixed-methods design was employed. Qualitative data were collected through interviews, focus group discussions, and classroom observations. In contrast, quantitative data were obtained from an ATEM-based self-efficacy questionnaire administered to 56 undergraduate students and analyzed descriptively. The findings revealed that students experienced low self-efficacy in several internal dimensions, including problem-solving orientation, mastery experiences, and the use of peer models in vocabulary learning. In contrast, students showed a strong reliance on external reinforcement, particularly reward–punishment mechanisms. These results indicate an imbalance between students' internal self-regulation and their dependence on external support in learning Arabic vocabulary. The study suggests that difficulties in vocabulary learning are influenced not only by instructional factors but also by learners' psychological readiness before the intervention. Practically, Arabic vocabulary instruction should provide authentic mastery experiences, meaningful modeling opportunities, and strategies that foster learner autonomy and self-regulation. Overall, the findings highlight the importance of conducting self-efficacy needs analyses before implementing instructional innovations in AFL contexts.